2017
DOI: 10.1098/rsbl.2016.0630
|View full text |Cite
|
Sign up to set email alerts
|

Incompressible fluid plays a mechanical role in the development of passive muscle tension

Abstract: Over short time scales, muscle fibres maintain a nearly constant volume of intracellular fluid. This fluid is essential to normal biochemical function, but its role in determining the mechanical properties of muscle has been considered in only a few theoretical analyses. Here we investigate the mechanical role of fluid in a fundamental property of muscle, its development of passive tension in response to stretch. We test a model of muscle structure in which incompressible fluid directly influences passive tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 18 publications
6
40
1
Order By: Relevance
“…Changes in muscle volume may alter the force generating potential of muscle. Studies on isolated muscles have demonstrated an increase in passive muscle tension with increased muscle fluid volume (Sleboda & Roberts, 2017). Passive muscle force at a given length changes in proportion to volume change, and a measurable change in force can be observed with volume changes as small as 5% in isolated muscles (Sleboda, Wold, & Roberts, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in muscle volume may alter the force generating potential of muscle. Studies on isolated muscles have demonstrated an increase in passive muscle tension with increased muscle fluid volume (Sleboda & Roberts, 2017). Passive muscle force at a given length changes in proportion to volume change, and a measurable change in force can be observed with volume changes as small as 5% in isolated muscles (Sleboda, Wold, & Roberts, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, for example, fluid flows are crucial in the regulation of ion concentrations and pH, which affect muscle contraction and hence force development during exercise (Sjogaard & Saltin, 1982). In addition to the importance of muscle fluids for the biochemistry of muscle contraction, recent studies suggest that fluid plays important mechanical roles within muscle, influencing passive force development during stretch (Gindre, Takaza, Moerman, & Simms, 2013; Sleboda & Roberts, 2017), work production during active contraction (Azizi, Deslauriers, Holt, & Eaton, 2017), and dynamic changes in muscle shape that influence muscle speed and force (Azizi, Brainerd, & Roberts, 2008; Eng, Azizi, & Roberts, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…How energy is stored during cocking remains unclear. We suspect stretching of elastic elements in muscle [31] and tendon or flexing of propodal cuticle as in stomatopod raptorial limbs [2].…”
Section: Muscle Insertion and Power Amplificationmentioning
confidence: 97%
“…More recent work suggests that a drop in the force capacity of a muscle during transverse loading may relate more to changes in internal pressure resulting in changes in the lattice spacing of myofibrils (Siebert et al 2016). In addition, the development of fluid pressure inside a muscle has been shown to interact with surrounding collagen fibers to contribute to longitudinal forces (Sleboda and Roberts 2017). Continued focus on transverse loading will advance our understanding of how structures like intramuscular connective tissues, aponeuroses, adjacent muscles, or skeletal elements may influence muscle performance.…”
Section: Discussionmentioning
confidence: 99%
“…This radial expansion requires a contracting muscle fiber to interact with the collagenous network of the ECM (Purslow 1989). Recent work has also shown that an increase in muscle volume resulting in radial expansion facilitates a mechanical interaction between intramuscular fluid and the ECM, thereby contributing to the development of passive force (Sleboda and Roberts 2017). Similarly, models have shown that the radial loading of helically oriented collagen fibers of the fibers of the ECM can directly influence longitudinal force (Gindre et al 2013).…”
Section: Introductionmentioning
confidence: 99%